Advanced Directives in Cancer Patients in Brazil - Freitas, Eni Devay de; Correia, Cristina Damasceno (Seven Editora, 2023)
Cancer is a health problem in the world. Scientific advances and precision medicine have demonstrated how cancer is a heterogeneous disease, requiring diagnostic, prognostic, and therapeutic individualiza-tion and personalization as well as more effective communication between doctors, patients, and fami-lies, to allow patients to express care preferences. The prevalence of AD in cancer patients varies widely among countries and Brazil has a paucity of data on Advance Directives (AD). OBJECTIVE: This study aims to describe the perception of cancer patients about topics such as Palliative Care (PC), Advance Care Planning (ACP), and Advance Directives (AD) in their oncologic care. METHODS: This was an observational, descriptive, cross-sectional study with cancer patients undergoing outpatient treatment in a private tertiary teaching and research hospital in the city of Salvador, Brazil. RESULTS: of the 50 patients involved, 37 answered the complete questionnaire; 18% of the patients refused to participate when they became aware of the content involving the themes PC and AD. Most of the participants were women, with higher education levels, a mean age of 64 years, and more than one year of oncolog-ic follow-up. More than 70% had not heard about Palliative Care (PC) and 78% were not approached about refractory conditions to treatment and ACP by their oncologist. Only 10.8% understood the terms Advance Directives (AD) or Living Will and only 8% had AD before cancer diagnosis. CONCLUSION: 90% of the patients did not know about AD. Advance Directives were not a topic of discussion between patients and physicians. DOI:https://doi.org/10.56238/devopinterscie-190